O uso da reabilitação bucal como meio de conscientização em saúde geral: reabilitação por prótese ocular - Carvalho, Cristiana Nassar [UNESP] (2015)
Eye loss results on facial asymmetry compromising its aesthetics affects the social life of pacients. Ocular prostheses are important to re-establish aesthetics; protect the anophthalmic cavity; recover function such as the redirection of lachrymatory liquid; and reintegrate the patient to society. The multidisciplinaire approach provide the best possible rehabilitation in order to minimize the impact of this situation. The aim of this study was to describe a case report, demonstrating clinical and laboratorial procedures for confection of ocular prostheses and highlighting their advantages. A female patient which loss of her eye was rehabilitation with an individualized artificial eye in acrylic resin restoring patient’s aesthetic and facial contour. The patient was satisfied with the treatment.